Aplikasi Knowledge Sharing untuk Kegiatan Marketing Berbasis Android di PT. Maha Global Persada Jakarta - Nandi, Mochamad; Maruloh, Maruloh (LPPM STMIK ANTAR BANGSA, 2017)
Abstract— Knowledge is one of the things that are important to an organization or company. To protect company knowledge, trying to keep knowledge in question, one of them by applying Knowledge Management System, one of the management of the KMS can be done is by way of share pegetahuan. The management of knowledge sharing in terms of gaining knowledge or knowledge sharing, has become a Global concern, PT Persada Supreme, especially in terms of marketing. Often sales who resigned, making the company must transfer knowledge to new sales. It is becoming increasingly difficult as more active sales outside causing lack of time to conduct information exchange between sales. The purpose of this research is to build applications that can provide ease in sharing knowledge between head of sales with sales or sales with sales of other, so expect the process of knowledge transfer can run faster. This research uses the methodology of the waterfall in the design of application development, while for application design researchers use Unified Modeling Language .